Integrating differentiated instruction & understanding by design : connecting content and kids - Tomlinson, Carol A. (Association for Supervision and Curriculum Development, 2006)
Explains how the combination of the Differentiated Instruction and Understanding by Design frameworks can ensure all students are learning at maximum levels. Describes how a curriculum built on the goal of student understanding, integrated with instructional approaches that emphasize reaching every learner, can provide teachers with more specific teaching targets and more flexible ways to reach them.